International implications of the United States Telecommunications Act. - COMOR, Edward A. (1997)
Describes the new Telecommunications Act as a significant step towards the liberalization of both domestic and overseas communications and information activities. Argues that in the short term, corporate and market forces will generate an intensification of market liberalization pressures overseas. In the long term, such pressures could promote a more volatile world order.